Method of Lower and Upper Solutions for Elliptic Systems with Nonlinear Boundary Condition and Its Applications - Ruyun Ma; Ruipeng Chen; Yanqiong Lu (Journal of Applied Mathematics)
We develop the method of lower and upper solutions for a class of elliptic systems with nonlinear boundary conditions. As its application, an elliptic system modeling a population divided into juvenile and adult age groups is studied, and we find sufficient conditions in terms of the principal eigenvalue of the corresponding linearized system, to guarantee the existence of coexistence states of the above juvenile-adult model.